Mitral stenosis with high left ventricular diastolic pressure. Issue 4 (April 1979) - Traill, T A; St John Sutton, M G; Gibson, D G
Abstract : Three patients with mitral stenosis are described, in whom the haemodynamic findings at cardiac catheterisation were more suggestive of left ventricular myocardial disease, in that the left ventricular diastolic pressure was high and the mitral valve gradient small. However, their echocardiograms showed abnormal wall movement during diastole characteristic of severe inflow obstruction, with slow and protracted filling, and at operation mitral stenosis was confirmed. Left ventricular wall stress was estimated throughout the cardiac cycle in one patient, and the diastolic stress-strain relation shown to be abnormal. The effects of mitral stenosis on left ventricular function are complex, and are not explicable simply by reduction in size of the mitral orifice.